Calidoscópio: experiências de artistas-professores como eixo para uma história do ensino de artes plásticas em Fortaleza. - Machado, Gilberto Andrade (2008)
The objective of this paper is to trace the history of the teaching of plastic arts in Fortaleza, taking into account the experience of some plastic artists who became teachers. We have opted for a time span which starts with the creation of the Plastic Arts Society of Ceará (SCAP), and ends in 2005 with the graduation of the first plastic artists from a public institution in Fortaleza. Our main goal was to investigate the meaning the plastic artists conferred to their teaching experience. It was our interest to identify some of the venues for the vocational training of plastic artists in Fortaleza; to learn how these artists perceived the act of teaching/learning arts; how they dealt with family and personal expectations on the artistic career, especially, how other knowledge of his social and political practice have incorporated to the teaching activity. In order to reach such objectives, we made use of oral history as a methodological resource by interviewing ten artists whose narratives are the main axis that support our historiographic organization. These narratives allow us to know how the cities were in the period of study, the social-cultural opportunities to which they had access and the school context when the artists started as students. The eager wish for a career training school for plastic artists in Fortaleza has been suppressed for several generations since the 1950´s, but it has been carried out in the early 2000´s. In the meantime, several attempts for a school have been allocated in public and private institutions, with the participation of the most experienced artists who discussed a model for teaching arts. We got to the conclusion that the present challenge for the plastic arts schools is to set goals for the training of an artist, where the career through education is not compulsory. For this, it is essential that the plastic artist who wishes to become a teacher be guided to produce more consistent reflection on his aesthetic experience. Knowing how to articulate with managers, coordinators and other teachers at the formal school, perhaps is the greatest challenge for the artist who proposes to be a teacher.